Mendeley-Assisted PTK Writing Assistance for Teachers of SMKN 1 Mempura Siak: Pendampingan Penulisan PTK Berbantuan Mendeley Untuk Guru SMKN 1 Mempura Siak - Lisnawita, Lisnawita; Asril , Elvira; Muzdalifah , Indah (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2024)
Teachers are expected to be able to articulate creative ideas and research findings arising from diverse difficulties encountered in the field toimprove the quality of learning both within and outside the classroom. This document serves as a reference andunique requirementfor teachers managing promotions. However, many teachers struggle with writing scientific papers because one of the conditions for their promotion is to produce scientific papers that will be published in a journal. The purpose of this paper is to provide answers for teachers who are makingscientific papers. The Mendeley desktop application can help teachers compile references and bibliographies in article papers. This activitywas conductedat SMKN 1 Mempura. This activity is carried out through the use of theory and practice. The outcome of this activity was that the teacher responded positively, gained new knowledge about the Mendeley program, and earnedbenefits in writing PTK.It is evident from one of the teachers who was able to publish his scientific work in the Dinamisia Journal after participating in this PKM activity